Stakeholder Synergy For Sustainable Tourism - Rahayu Sulistiowati; A. Fachrezi Adisa; Susana Indriyati Caturiani (Goodwood Publishing, 2021)
Purpose: This study aims to describe the synergy between stakeholders in revitalizing tourist destinations to support sustainable tourism in Way Tebabeng, North Lampung. Methods: The research was conducted using a descriptive-qualitative approach, and the data collection techniques are in the form of interviews, observations, and documentation. Results: The results show that the synergy of stakeholders is not optimal due to the one-way communication, leading to coordination which only takes place at the beginning. The inhibiting factors for the revitalization of the Way Tebabeng destination are the lack of budget, leaders, and human resource factors. Limitation: This study uses a qualitative approach with a limited level of generalization. Therefore, it should be reviewed with other approaches and wider research locations. Contribution: The revitalization of tourism destinations in terms of synergy between stakeholders was reviewed as the basis for developing policies, especially in local communities.